Strength Characteristics of Concrete with Indian Mettakaolin and Rice Husk Ash - Swaminathen, A.N.; ravi, S.Robert (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Concrete is the most extensively used construction material around the world and its properties have been undergoing changes through technological advancements. Varieties of concrete have been developed to enhance the different properties of concrete. An investigation in to the potential use of partial replacement of mineral admixture in high performance concrete (HPC) has carried out. The engineering properties of fresh and hardenedconcrete are obtained by conducting test on slump, vee-bee, compaction factor and compressive strength, flexural strength, spilt tensile strength and modulus of elasticity, in this project partial replacement of cement bymetakaolin and rice husk ash been used for varying replacement of 0+0%, 5+105, 7.5+10%,10+10%,5+12.5%, 10+12.5%, 5+15%, 7.5+15%, and 10+15%for high strength, workability and also an eco-friendly by less emission of co2. It has been concluded that strength development of concrete blended with metakaolin and rice hush ash was enhanced. It was found that in 7.5% replacement of metakaolin and 12.5% replacement of rice husk ash appear to be the optimum replacement which exhibited more strength. This investigation has proved that the MK and RHA concrete can be used as structural concrete at suitable replacement percentage.